Vulnerability of Nyabarongo River Water Abstraction to Climate Change in Rwanda - Manikuze, Prosper; Nyongesah, John (International Journal of Environmental Sciences, 2023)
Purpose: Climate change in Rwanda is a great challenge resulting from increased temperature and causing abnormal variability in weather variables and threatening the socio-economic welfare of human beings. Water resources have been subjected to degradation and pollution due to intensive and frequent rainfall that have negatively impact on water abstractions in their proximity. This study aimed at analyzing the vulnerability of the Nyabarongo river water abstraction to climate change. Methodology: GIS and remote sensing were used to map and analyze possible changes in geophysical status of the river. Secondary data collection on temperature and rainfall for a forty years period was used to analyze the trend in climate change in Rwanda. Findings: The results indicated that climate change in Rwanda has resulted in extreme weather events that resulted in inundations and floods of Nyabarongo River and its wetland that exacerbated the changes in geophysical status such as river flow pathway and meandering. This has resulted in washing away of some water abstraction facilities around the river and the distancing from such facilities leading to interference with abstraction. It was also found out that dry season's markedly diminished water available for abstraction in the river and impacting negatively on the groundwater recharge. Unique Contribution to Theory, Practice and Policy: The findings can stimulate decision makers in water resources management to initiate and roll out similar studies countrywide and serve as baseline to adopt measures and strategies for the sustainable management of the resources. The findings also call for Water users to take into consideration of climate impacts during the studies, designs and implementation of water use project for the sustainable exploitation of water resources.